Complaints of reduced cognitive functioning during perimenopause: a cross-sectional analysis of the Japan Nurses' Health Study - Kunihiko Hayashi; Yuki Ideno; Kazue Nagai; Jung-Su Lee; Toshiyuki Yasui; Takumi Kurabayashi; Kiyoshi Takamatsu (BMC, 2022)
Abstract Background Many women experience various symptoms during the period of menopausal transition, including complaints of reduced cognitive functioning. However, these complaints are not necessarily recognized as core menopausal symptoms. In this study, we sought to characterize subjective complaints of reduced cognitive functioning by analyzing cross-sectional data from the Japan Nurses' Health Study (JNHS). Methods The JNHS 4-year follow-up questionnaire containing a 21-item climacteric symptom checklist, which included a question about "poor memory or forgetfulness", was mailed between 2005 and 2011 to all JNHS participants, regardless of their age at the time of the survey. We estimated the prevalence of slight and severe complaints in 5-year age-groups. We used principal component analysis to explore the underlying factors among the 21 symptoms during the menopausal transition period in women aged 45-54 years at the time of the survey. We also examined risk factors for complaints using multivariable modified Poisson regression analysis. Results In total, 12,507 women responded to the 4-year survey. The mean age at the time of the 4-year survey was 46.5 years (range 27-82). "Poor memory or forgetfulness" showed a peak prevalence of 81.7% (severe 27.9%; slight 53.8%) at 50-54 years, and gradually decreased after 55 years. Principal component analysis indicated that "poor memory or forgetfulness" belonged to somatic symptoms and was close to psychological symptoms in women aged 45-54 years. In women aged 45-54 years, the complaint was also significantly associated with hot flashes and sweats. Multivariable modified Poisson regression analysis showed that menopausal status (uncertain and postmenopausal), less sleep (sleep of < 5 h and sleep of 5- < 6 h), night-shift work, and severe vasomotor symptoms (VMS) were significantly associated with the prevalence of severe complaints of reduced cognitive functioning in women aged 45-54 years. Conclusions We found that prevalence of "poor memory or forgetfulness" was highest during the menopausal transition period and among perimenopausal women. This subjective complaint was associated with somatic, psychological complaints and VMS. It may be useful for women with cognitive problems in the transition period to consider management of comorbid menopausal symptoms.